The specific absorption rate investigation of different mobile technologies from commercial mobile phones [electronic resource] - Muhammad Hafidz Al Azizi Amin Al Hafidz, 1993- , author (2016)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2016